IMPLEMENTATION OF THE SIUUL MODEL IN DEVELOPING SPEAKING SKILLS THROUGH ROLE-PLAYING CENTERS IN CHILDREN AGED 4-5 YEARS AT SPSN BALE PLAYING ABDI PRAJA CILINCING NORTH JAKARTA - Siti Sahlia; Yuli herlina; Fatmi Cahyani; Karen Sunandar; Sri Watini (Sean Institute, 2023)
Early childhood development is an important period starting from 1000 days of life to 5 years where synapses develop rapidly so that there needs to be the right stimulus to support and improve their abilities, especially in speaking with the SIUUL model. This study aims to determine the improvement of speech skills in children through the siuul method in the role-playing center in group B at SPSN Bale Play Abdi Praja, This type of research is classroom action research. The subjects of the study were Group B students aged 4-5 years SPSN Bale Play Abdi Praja, Cilincing District, data on speaking ability were collected through observation activities. The type of research in this PTK paper is classroom Action Research with 3 three cycles. The 1st cycle was observed and played with hand and finger puppets during role-playing activities Results based on the results of the research action obtained results on the 3rd us cyclewhich was 86.6% . With the results of 13 children who developed or Developed as expected from 15 children Keywords : SIUUL Method, Speaking Ability, Role Playing Center